2020
DOI: 10.1177/1559325820970810
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Promote Stem Cells Regeneration and Repair Acinar Cells in L-arginine / Radiation -Inducing Chronic Pancreatitis in Rats

Abstract: Objective: Chronic Pancreatitis (CP) is a multifactorial disease. It was characterized by severe inflammation and acinar cell destruction. Thus, the present study was initiated to evaluating the ability of bone marrow-based mesenchymal stem cell (MSCs) combined with Icariin to restore and regenerate acinar cells in the pancreas of rats suffering chronic pancreatitis. Methods: Chronic pancreatitis was induced in rats via both L-arginine plus radiation, repeated L-arginine injection (2.5g/Kg body-weight, 1, 4,7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Significance at P < 0.01 The mechanism of chronic pancreatitis induction by l-arginine was explained by (16,17) agreed with some investigators (16,18,19) and explained by others (17,20)…”
Section: Table (3)supporting
confidence: 78%
“…Significance at P < 0.01 The mechanism of chronic pancreatitis induction by l-arginine was explained by (16,17) agreed with some investigators (16,18,19) and explained by others (17,20)…”
Section: Table (3)supporting
confidence: 78%
“…Icariin and icaritin have also been reported to inhibit UVB-induced photoaging by activating Nrf2/ARE signaling, suppressing JNK’s and ERK’s phosphorylation as well as NF-ĸB’s expression [ 138 ]. In a recent study, icariin was found to significantly increase bone marrow mesenchymal stem cells (MSCs) regeneration and repair pancreatic injury in L-arginine/γ-ray-caused rat model of chronic pancreatitis [ 139 ].…”
Section: Pharmacodynamics Of Icariin After Radiation Exposurementioning
confidence: 99%
“…Owing to no organ other than the pancreas appears to be impaired by L-arginine and it does not require surgery intervention. 10 A few studies have evaluated potential role of MSCs in chronic pancreatitis’, in which the persistence and consequences of the inflammatory response led to the formation of the extensive fiber region, as a change of pancreatic stellate cell (PSC) to myofibroblast shape. Establishing fibrotic region as a replacement for glandular parenchyma, thus minimizing pancreatic functionality.…”
Section: Introductionmentioning
confidence: 99%